THE ADMINISTRATIVE POLICIES AND CHALLENGES OF MOHAMMAD BIN TUGHLUQ - Tanveer Ahmad Kuchay (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Mohammad Bin Tughluq's reign in the 14th century Delhi Sultanate was marked by significant historical context and political challenges. Faced with economic issues, regional rebellions, and external pressures, Tughluq implemented ambitious administrative policies aimed at centralizing power and extending the Sultanate's authority. However, these policies often led to unintended consequences and widespread discontent. The introduction of token currency and the capital's relocation to Daulatabad caused economic turmoil and social upheaval, eroding public trust and stability. Additionally, Tughluq's administrative reforms faced challenges of corruption, mismanagement, and resistance, hindering effective governance. The consequences of his policies resulted in economic instability, displacement of populations, exploitation of farmers, and a decline in regional autonomy. Tughluq's reign serves as a cautionary tale, highlighting the intricate interplay between historical context, political ambitions, and decision-making consequences. It influenced subsequent rulers' strategies and shaped the historical development of the Delhi Sultanate, emphasizing the need for careful consideration of socio-economic implications and balancing central authority with regional cooperation for effective governance.